Ultra-high molecular weight silicone-modified acrylate emulsion and preparation method thereof

The ultra-high molecular weight silicone modified acrylate emulsion prepared by using core-shell emulsion polymerization technology as the binder for the negative electrode of lithium-ion batteries, the problem of expansion of silicon-based materials in lithium-ion batteries is solved, and the circulation and safety performance of the battery is significantly improved.

CN116003695BActive Publication Date: 2025-05-02SHENZHEN HAODYNE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211711537.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-05-02
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

Silicon-based materials expand severely during the charging and discharging cycle of lithium-ion batteries, causing cracking and powdering of active materials, limiting their use in lithium-ion batteries.

Method used

The ultra-high molecular weight silicone modified acrylate emulsion prepared by core-shell emulsion polymerization technology is used as the binder for silicon-based, silicon/carbon-based negative electrodes. Through its special core-shell structure and bilayer silicone structure, the mechanical strength of the negative electrode is enhanced and the expansion of silicon is suppressed.

Benefits of technology

It significantly improves the circulation performance of lithium batteries, extends service life, and improves the stability and safety performance of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004027756000000011
    Figure BDA0004027756000000011
  • Figure BDA0004027756000000021
    Figure BDA0004027756000000021
  • Figure BDA0004027756000000031
    Figure BDA0004027756000000031
Patent Text Reader

Abstract

The invention discloses an ultra-high molecular weight organosilicon-modified acrylate emulsion and a preparation method thereof. The ultra-high molecular weight organosilicon-modified acrylate emulsion comprises a core layer emulsion and a shell layer emulsion, wherein the core layer emulsion comprises a structural monomer, an acidic monomer, a silane coupling agent, etc., and the core-shell emulsion comprises a structural monomer, an acidic monomer, an organosilicon polymer, etc.; the preparation method of the ultra-high molecular weight organosilicon-modified acrylate emulsion comprises: step one, preparing a core layer emulsion, step two, preparing a shell layer pre-emulsion, and step three, slowly dropping the shell layer pre-emulsion into the core layer emulsion to prepare the ultra-high molecular weight organosilicon-modified acrylate emulsion. The ultra-high molecular weight organosilicon-modified acrylate emulsion of the invention has a special core-shell structure, and when used as a binder, it can achieve more effective bonding to the negative electrode, can more effectively inhibit the expansion of silicon, improve the cycle performance of the lithium battery, and improve the overall stability and safety of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium batteries, and in particular to an ultra-high molecular weight organosilicon-modified acrylate emulsion and a preparation method thereof. Background Art

[0002] Lithium batteries are mainly composed of positive electrodes, negative electrodes, separators and electrolytes. The positive and negative electrode materials of lithium batteries are generally powdered solids. When preparing the positive or negative electrodes, a binder is required to bond them into a whole.

[0003] Nowadays, the preparation material of the negative electrode is generally graphite-based carbon. When preparing the negative electrode, the graphite-based carbon-based solid powder, binder, conductive agent, etc. are mixed evenly and then coated on the metal foil. After drying, rolling, cutting and other process treatments, the negative electrode is obtained. The theoretical specific capacity of graphite-based carbon is only 372mAh / g, which leads to an increase in the volume and weight of the battery when the battery with graphite-based carbon as the main material needs a larger capacity. Currently, the material with the highest specific capacity among the known negative electrode materials is silicon, and the theoretical specific capacity of silicon is as high as 4200mAh / g. However, the volume of silicon-based materials expands by as much as 300-400% during the charge and discharge cycle process, which will generate great stress inside the battery, causing the active material to crack and pulverize, which seriously limits the use of silicon-based materials in lithium-ion batteries.

[0004] Various research experiments have found that changing the structure of silicon-based materials themselves or compounding them with other materials cannot effectively solve the expansion problem of silicon-based materials. Therefore, it is urgent to find ways to control the expansion rate of silicon-based materials from other channels. Summary of the invention

[0005] In order to further suppress the expansion rate of silicon-based materials, the present application provides an ultra-high molecular weight silicone-modified acrylate emulsion and a preparation method thereof. This ultra-high molecular weight silicone-modified acrylate emulsion is polymerized using core-shell emulsion polymerization technology and has an ultra-high molecular weight. When used as a binder for silicon-based and silicon / carbon-based negative electrodes, it can effectively improve the mechanical strength of the negative electrode. At the same time, because it has a special core-shell structure with a silane coupling agent in the core layer and a silicone polymer in the shell layer, it can achieve more effective bonding to the negative electrode, more effectively suppress the expansion of silicon, improve the cycle performance of the lithium battery, and improve the overall stability and safety of the lithium battery.

[0006] In the first aspect, the present application provides an ultra-high molecular weight silicone-modified acrylate emulsion using the following technical solution:

[0007] An ultra-high molecular weight organosilicon-modified acrylate emulsion, wherein the ultra-high molecular weight organosilicon-modified acrylate emulsion is polymerized by core-shell emulsion polymerization technology, and the ultra-high molecular weight organosilicon-modified acrylate emulsion comprises a core layer emulsion and a shell layer emulsion, wherein the core layer emulsion comprises the following raw materials in parts by weight:

[0008]

[0009] The shell emulsion comprises the following raw materials in parts by weight:

[0010]

[0011] The structural monomers in the core layer emulsion and the shell layer emulsion are a combination of one or more of methyl acrylate, ethyl acrylate, isobutyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, isobornyl acrylate, methyl methacrylate, butyl methacrylate, acrylonitrile, acrylamide, styrene, vinyl acetate, and isobornyl methacrylate;

[0012] The acidic monomers in the core layer emulsion and the shell layer emulsion are maleic acid, cinnamic acid, citric acid and maleic anhydride, which are compounded in a mass ratio of 3: (1-2): (0.5-1): (3-5).

[0013] In the above technical solution, the silane coupling agent is a kind of highly reactive organic silicon compound composed of silicon atoms, functional organic groups and hydrolyzable active groups. The functional organic groups contained in the silane coupling agent can react with related types of polymers by affinity, and the hydrolyzable groups contained in the silane coupling agent can form chemical bonds with the surface of the polar substrate after hydrolysis and condensation, or produce chemical crosslinking, thereby achieving the effect of enhancing its viscosity.

[0014] Silicone polymer is a kind of polymer material with a similar silicon-oxygen polymer skeleton and organic side chains such as methyl, phenyl, vinyl, alkoxy, etc. Its molecular chain is flexible and the bond energy of the silicon-oxygen bond it contains is high. Its polymer structure gives it excellent properties such as adaptability to large temperature differences, low surface energy, low dielectric loss, and aging resistance.

[0015] The ultra-high molecular weight silicone-modified acrylic emulsion prepared by the above technical scheme has a special core-shell structure. When used as a binder for preparing silicon-based and silicon / carbon-based negative electrodes, it has excellent adhesion, can be evenly dispersed and mixed with active materials and conductive agents, and can improve the initial coulomb efficiency of silicon-based negative electrodes. At the same time, because it has a special double-layer silicone core-shell structure, it can further combine with silicon-based negative electrodes or silicon / carbon-based negative electrodes through the silicon atoms it contains, and further increase the chemical crosslinking amount of its negative electrode substrate through the alkoxy structure it contains, thereby enhancing the mechanical strength of the negative electrode, effectively inhibiting the volume expansion of silicon, buffering the mechanical stress during the volume expansion of silicon, reducing the solid electrolyte intermediate phase produced by the contact reaction of silicon with the electrolyte during the continuous expansion process, effectively eliminating the side reactions caused by the unstable solid electrolyte intermediate phase, significantly improving the cycle performance of the lithium battery, effectively extending the service life of the lithium battery, and improving the safety performance of the lithium battery.

[0016] The hydrolyzable groups contained in the silane coupling agent can react with each other after hydrolysis to form a stable multi-molecular structure of the silane coupling agent, which will cause the core layer structure to be too dense, inhibit the penetration of the shell layer emulsion into the core layer emulsion, and inhibit the further cross-linking reaction between the core layer emulsion and the shell layer emulsion, resulting in reduced stability of the core-shell structure. It will also further reduce the silanol formed after the hydrolyzable groups contained in the silane coupling agent are hydrolyzed to form an oxane bond with the metal hydroxyl group on the surface of the negative electrode, reducing the amount of chemical cross-linking between the emulsion and the negative electrode, thereby resulting in the ultra-high molecular weight silicone-modified acrylate emulsion and the silicon-based negative electrode or silicon / carbon-based negative electrode. The bonding force is reduced. The acidic monomer compounded in the above technical scheme according to the mass ratio of maleic acid, cinnamic acid, citric acid and maleic anhydride is 3: (1-2): (0.5-1): (3-5) has the effect of inhibiting the mutual reaction of the silane molecules on the silane coupling agent, thereby reducing the mutual reaction of the hydrolyzable groups contained in the silane coupling agent after hydrolysis, further promoting the chemical crosslinking amount of the ultra-high molecular weight silicone modified acrylate emulsion and the silicon-based negative electrode or the silicon / carbon-based negative electrode, and further improving the bonding force of the ultra-high molecular weight silicone modified acrylate emulsion to the silicon negative electrode when used as a binder.

[0017] Preferably, the core layer emulsion comprises the following raw materials in parts by weight:

[0018]

[0019] The shell emulsion comprises the following raw materials in parts by weight:

[0020]

[0021] The structural monomers in the core layer emulsion and the shell layer emulsion are a combination of one or more of ethyl acrylate, butyl acrylate, 2-isooctyl acrylate, isobornyl acrylate, methyl methacrylate, butyl methacrylate and acrylonitrile.

[0022] In the above technical scheme, the core-shell structure of the double-layer silicone of the ultra-high molecular weight silicone-modified acrylic emulsion prepared according to the above formula is polymerized more stably. When used as a binder for preparing silicon-based and silicon / carbon-based negative electrodes, it has better adhesion, further enhances the mechanical strength of the negative electrode, more effectively inhibits the volume expansion of silicon, buffers the mechanical stress during the volume expansion of silicon, further reduces the generation of unstable solid electrolyte intermediate phases, improves the overall cycle performance of lithium batteries, and improves the safety of lithium batteries.

[0023] Preferably, the silane coupling agent is a combination of one or more of methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, methylallyltrimethoxysilane and vinyltriacetoxysilane.

[0024] In the above technical scheme, the use of the above-mentioned silane coupling agent can further enhance the bonding force between the silicon atoms contained in the ultra-high molecular weight silicone-modified acrylate emulsion and the silicon-based negative electrode or the silicon / carbon-based negative electrode, further enhance the chemical crosslinking amount between the alkoxy structure contained therein and the negative electrode substrate, build a rigid skeleton of the negative electrode, and enhance the mechanical strength of the negative electrode.

[0025] Preferably, the organosilicon polymer is a compound of one or more of vinyl silane oligomer, vinyl MQ organosilicon resin, vinyl silicone rubber, vinyl silicone oil, methacryloxy silane oligomer, and acryloxy MQ silicone resin.

[0026] In the above technical solution, the high molecular weight silicone modified acrylate emulsion prepared by the above silicone polymer can more effectively bond the negative electrode substrate, improve the mechanical strength of the ultra-high molecular weight silicone modified acrylate emulsion, and better achieve the inhibition of silicon expansion.

[0027] The ultra-high molecular weight silicone-modified acrylate emulsion prepared by the above silicone polymer further enhances the uniform dispersion and mixing of the ultra-high molecular weight silicone-modified acrylate emulsion with the active material and the conductive agent, further promotes the homogeneity of the negative electrode slurry, and further promotes the uniform coating of the negative electrode slurry on the negative electrode substrate.

[0028] Preferably, the initiator is a combination of one or more of ammonium persulfate, potassium persulfate, sodium persulfate, and 2,2'-azobisisobutylamidine dihydrochloride.

[0029] Preferably, the initiator is ammonium persulfate, potassium persulfate and sodium persulfate mixed in a mass ratio of 7:(2-3):(2-5).

[0030] In the above technical scheme, the use of the initiator in the above proportion can better promote the preparation of ultra-high molecular weight silicone modified acrylic emulsion with core-shell structure, control the polymerization of shell emulsion monomers to occur on core particles, significantly increase the probability of shell emulsion wrapping core emulsion, achieve a stable core-shell structure, and further improve the stability of the emulsion.

[0031] Preferably, the emulsifier is a compound of alkyl polyoxyethylene ether ammonium sulfate, fatty alcohol polyoxyethylene ether sodium sulfosuccinate, and nonylphenol polyoxyethylene ether in a mass ratio of 5: (1-3): (2-5).

[0032] In the above technical scheme, the use of the above emulsifier to prepare the core-shell structured ultra-high molecular weight silicone modified acrylate emulsion has a better emulsification effect, significantly improves the coverage of the core-shell structured particles contained in the ultra-high molecular weight silicone modified acrylate emulsion, and further improves the stability of the emulsion.

[0033] Preferably, the solid content of the ultra-high molecular weight silicone-modified acrylate emulsion is 38% to 65%.

[0034] In the above technical solution, when the solid content of the ultra-high molecular weight silicone-modified acrylic emulsion is 38% to 65%, the interaction force between particles is appropriate, the viscosity and surface activity of the emulsion are suitable as a binder, and the stability of the emulsion is higher.

[0035] Preferably, the silane coupling agent is a combination of one or more of methacryloxypropyltrimethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane.

[0036] Preferably, the organosilicon polymer is a compound of one or more of vinyl silane oligomer, vinyl MQ organosilicon resin, vinyl silicone rubber and vinyl silicone oil.

[0037] In the second aspect, the present application provides a method for preparing an ultra-high molecular weight silicone-modified acrylate emulsion, which adopts the following technical scheme:

[0038] A method for preparing an ultra-high molecular weight silicone-modified acrylate emulsion comprises the following steps:

[0039] (1) mixing 30% to 50% of the emulsifier, 30% to 50% of deionized water, structural monomers, silane coupling agents, and acidic monomers in the core layer emulsion formula and mechanically stirring until milky white to obtain a core layer pre-emulsion;

[0040] (2) Under a nitrogen atmosphere, the remaining deionized water, initiator, and remaining emulsifier in the core layer emulsion formula are mixed and mechanically stirred and placed in a water bath, and then the core layer pre-emulsion is added dropwise thereto, the dropping time is controlled at 2h to 4h, and the reaction temperature is 70 to 80°C to obtain a core layer emulsion;

[0041] (3) mixing the emulsifier, deionized water, structural monomer, organosilicon polymer, and acidic monomer in the shell layer emulsion formula and mechanically stirring until milky white, to obtain a shell layer pre-emulsion;

[0042] (4) Add the initiator in the shell layer emulsion formula to the core layer emulsion, and then slowly add the shell layer pre-emulsion to the core layer emulsion, the dropping time is controlled at 2h to 4h, the reaction temperature is 70 to 80°C, and it is kept at 83 to 87°C for 1h, then cooled to room temperature, filtered and discharged, to obtain an ultra-high molecular weight silicone-modified acrylate emulsion.

[0043] In the above technical scheme, the ultra-high molecular weight silicone modified acrylate emulsion with a core-shell structure prepared by the above preparation method not only has the shell layer emulsion better wrapping the core layer emulsion, but also the shell layer emulsion has sufficient time to penetrate into the core layer emulsion, and a grafting reaction occurs between the core layer and the shell layer, further improving the bonding strength between the ultra-high molecular weight silicone modified acrylate emulsion and the silicon-based negative electrode or the silicon / carbon-based negative electrode.

[0044] Preferably, the reaction temperature in step (2) is controlled at 80°C;

[0045] The reaction temperature in step (4) is controlled at 80°C.

[0046] In the above technical scheme, the reaction temperature is controlled at 80°C, the shell layer emulsion can penetrate into the core layer emulsion more fully, the reaction between the core layer and the shell layer is more complete, and the prepared ultra-high molecular weight silicone modified acrylate emulsion has a more stable core-shell structure, and the binding force to the silicon-based negative electrode is further enhanced.

[0047] In summary, the present application includes at least one of the following beneficial technical effects:

[0048] 1. The ultra-high molecular weight silicone-modified acrylic emulsion prepared by the above technical solution has a special core-shell structure. When used as a binder for preparing silicon-based and silicon / carbon-based negative electrodes, it has excellent adhesion, can be evenly dispersed and mixed with active materials and conductive agents, and can improve the initial coulomb efficiency of silicon-based negative electrodes. At the same time, because it has a special double-layer silicone core-shell structure, it can further combine with silicon-based negative electrodes or silicon / carbon-based negative electrodes through the silicon atoms it contains, and further increase the chemical crosslinking amount of its negative electrode substrate through the alkoxy structure it contains, thereby enhancing the mechanical strength of the negative electrode, effectively inhibiting the volume expansion of silicon, buffering the mechanical stress during the volume expansion of silicon, reducing the solid electrolyte intermediate phase produced by the contact reaction of silicon with the electrolyte during the continuous expansion process, effectively eliminating the side reactions caused by the unstable solid electrolyte intermediate phase, significantly improving the cycle performance of the lithium battery, effectively extending the service life of the lithium battery, and improving the safety performance of the lithium battery.

[0049] 2. The acidic monomer compounded in the mass ratio of maleic acid, cinnamic acid, citric acid and maleic anhydride of 3:(1-2):(0.5-1):(3-5) has the effect of inhibiting the mutual reaction of the silane molecules on the silane coupling agent, thereby reducing the mutual reaction of the hydrolyzable groups contained in the silane coupling agent after hydrolysis, further promoting the chemical crosslinking amount of the ultra-high molecular weight silicone modified acrylate emulsion and the silicon-based negative electrode or the silicon / carbon-based negative electrode, and further improving the bonding force of the ultra-high molecular weight silicone modified acrylate emulsion to the silicon negative electrode when used as a binder.

[0050] 3. The use of an initiator prepared in a mass ratio of ammonium persulfate, potassium persulfate, and sodium persulfate of 7:(2-3):(2-5) can better promote the preparation of an ultra-high molecular weight silicone-modified acrylate emulsion with a core-shell structure, control the polymerization of the shell emulsion monomer to occur on the core layer particles, significantly increase the probability of the shell emulsion wrapping the core layer emulsion, achieve a stable core-shell structure, and further improve the stability of the emulsion.

[0051] 4. The core-shell structured ultra-high molecular weight silicone modified acrylate emulsion is prepared by using an emulsifier prepared by mixing alkyl polyoxyethylene ether ammonium sulfate, fatty alcohol polyoxyethylene ether sodium sulfosuccinate, and nonylphenol polyoxyethylene ether in a mass ratio of 5:(1-3):(2-5). The emulsifying effect is better, the coverage of the core-shell structured particles contained in the ultra-high molecular weight silicone modified acrylate emulsion is significantly improved, and the stability of the emulsion and the uniformity of the dispersion of the emulsion particles in the emulsion are further improved. DETAILED DESCRIPTION

[0052] An ultra-high molecular weight silicone-modified acrylate emulsion and a preparation method thereof will be further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto.

[0053] Examples 1-3

[0054] An ultra-high molecular weight silicone-modified acrylic emulsion, the formula of which is shown in Table 1:

[0055] Table 1 Amount of each component in the formula of Examples 1-3

[0056]

[0057]

[0058] The silane coupling agent of Example 1-3 is a compound of methacryloxypropyltrimethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane in a mass ratio of 1:1:1.

[0059] The organosilicon polymer of Examples 1-3 is a compound of vinyl silane oligomer, vinyl MQ organosilicon resin, vinyl silicone rubber and vinyl silicone oil in a mass ratio of 1:1:1:1.

[0060] Example 1-3 Preparation of acidic monomers: Maleic acid, cinnamic acid, citric acid and maleic anhydride are compounded in a mass ratio of 3:1:1:5.

[0061] Example 1-3 Preparation of initiator: ammonium persulfate, potassium persulfate and sodium persulfate are compounded in a mass ratio of 7:2:5.

[0062] Preparation of emulsifier in Example 1-3: Alkyl polyoxyethylene ether ammonium sulfate, fatty alcohol polyoxyethylene ether sodium sulfosuccinate, and nonylphenol polyoxyethylene ether are compounded in a mass ratio of 5:3:2.

[0063] Example 1-3 Preparation of an ultra-high molecular weight silicone-modified acrylate emulsion:

[0064] Step 1) 35% of the emulsifier, 50% of deionized water, structural monomers, silane coupling agent, and acidic monomers in the core layer emulsion formula are mixed, and mechanically stirred at 200 r / min at 45° C. until milky white, to obtain a core layer pre-emulsion.

[0065] Step 2) Under a nitrogen atmosphere, the remaining 50% of deionized water in the core layer emulsion formula, 50% of the initiator in the core layer emulsion formula, and the remaining 65% of the emulsifier in the core layer emulsion formula are mixed, and mechanically stirred at 200 r / min for 10 min at 30°C, and then placed in a water bath at 80°C, and continued to be mechanically stirred at 220 r / min, and then the core layer pre-emulsion obtained in step 1 is added dropwise thereto at the same time. After 1 / 2 of the core layer pre-emulsion is added dropwise, the remaining 50% of the initiator in the core layer emulsion formula is added dropwise thereto at the same time. The core layer pre-emulsion is added dropwise for 4 hours, and the core layer emulsion is obtained after the addition is completed.

[0066] Step 3) The emulsifier, deionized water, structural monomer, silicone polymer and acidic monomer in the shell emulsion formula are mixed, and mechanically stirred at 180 r / min at 45° C. until milky white, to obtain a shell pre-emulsion.

[0067] Step 4) The core layer emulsion obtained in step 2 is placed in a water bath at 80°C and mechanically stirred at 220r / min. The initiator in the shell layer emulsion formula is then added to the core layer emulsion. The shell layer pre-emulsion obtained in step 3 is then slowly dripped into the core layer emulsion for 4 hours. After the dripping is completed, the solution is heated to 85°C and kept warm for 1 hour, then cooled to room temperature, and filtered with a 200-mesh filter to obtain an ultra-high molecular weight silicone-modified acrylate emulsion.

[0068] Embodiment 4-6

[0069] Preparation of an ultra-high molecular weight silicone-modified acrylate emulsion:

[0070] The difference from Example 1 is the input amount of each component in the formula, and the specific data are shown in Table 2.

[0071] Table 2 Amount of each component in the formula of Examples 4-6

[0072]

[0073] Example 4-6 Preparation of acidic monomers: Maleic acid, cinnamic acid, citric acid and maleic anhydride are compounded in a mass ratio of 3:2:0.5:3.

[0074] Example 4-6 Preparation of initiator: ammonium persulfate, potassium persulfate and sodium persulfate are compounded in a mass ratio of 7:3:2.

[0075] Example 4-6 Preparation of emulsifier: Alkyl polyoxyethylene ether ammonium sulfate, fatty alcohol polyoxyethylene ether sodium sulfosuccinate, and nonylphenol polyoxyethylene ether are compounded in a mass ratio of 5:1:5.

[0076] Example 7

[0077] The invention discloses a preparation method of an ultra-high molecular weight organosilicon-modified acrylic emulsion, which is different from that of Example 1 in the preparation of an initiator. The initiator is a compound of ammonium persulfate, potassium persulfate and sodium persulfate in a mass ratio of 1:1:1.

[0078] Example 8

[0079] The invention discloses a preparation method of an ultra-high molecular weight organosilicon-modified acrylic emulsion, which is different from that of Example 1 in the preparation of an emulsifier. The emulsifier is a compound of alkyl polyoxyethylene ether ammonium sulfate, fatty alcohol polyoxyethylene ether sodium sulfosuccinate, and nonylphenol polyoxyethylene ether in a mass ratio of 1:1:1.

[0080] Example 9

[0081] A preparation of an ultra-high molecular weight silicone-modified acrylate emulsion, which is different from Example 1 in that the water bath temperature in step 2 is changed from 80°C to 70°C; and the water bath temperature in step 4 is changed from 80°C to 70°C.

[0082] Example 10

[0083] The invention discloses a preparation method for an ultra-high molecular weight silicone-modified acrylic emulsion. The method is different from the embodiment 1 in that the silane coupling agent is a compound of methacryloxypropyltrimethoxysilane, allyltrimethoxysilane and vinyltriacetoxysilane in a mass ratio of 1:1:1.

[0084] Embodiment 11

[0085] The invention discloses a preparation method for an ultra-high molecular weight organosilicon-modified acrylate emulsion. The difference from Example 1 is that the organosilicon polymer is a compound of methacryloyloxysilane oligomer, vinyl silicone rubber, acryloxy MQ silicone resin and vinyl silicone oil in a mass ratio of 1:1:1:1.

[0086] Comparative Example 1

[0087] Preparation of an ultra-high molecular weight silicone-modified acrylate emulsion. The difference from Example 1 is that the silicone polymer in the formula of the shell emulsion is replaced by methyl acrylate in equal amounts.

[0088] Comparative Example 2

[0089] The invention discloses a preparation method for an ultra-high molecular weight silicone-modified acrylic emulsion. The difference from Example 1 is that the silane coupling agent in the formula of the core layer emulsion is replaced by methyl acrylate in equal amount.

[0090] Comparative Example 3

[0091] The invention discloses a preparation method for an ultra-high molecular weight silicone-modified acrylic emulsion. The difference from Example 1 is that the silicone polymer in the formula of the shell layer emulsion is replaced by a silane coupling agent in an equal amount, and the silane coupling agent in the formula of the core layer emulsion is replaced by a silicone polymer in an equal amount.

[0092] Comparative Example 4

[0093] The invention discloses a preparation method of an ultra-high molecular weight silicone-modified acrylic emulsion, which is different from that of Example 1 in the preparation of an acidic monomer. The acidic monomer is maleic acid, cinnamic acid, citric acid and maleic anhydride compounded in a mass ratio of 1:1:1:1.

[0094] Comparative Example 5

[0095] A preparation of an ultra-high molecular weight silicone-modified acrylate emulsion, which is different from Example 1 in that the water bath temperature in step 2 is changed from 80°C to 60°C; and the water bath temperature in step 4 is changed from 80°C to 60°C.

[0096] Experiment 1

[0097] Emulsion performance test

[0098] Appearance: 1 ml of the ultra-high molecular weight silicone-modified acrylate emulsion of each embodiment and comparative example was placed in a colorimetric tube, and the color (color caused by particle size: blue light) and uniformity (whether there is stratification or floccules) of the emulsion were visually inspected.

[0099] Mechanical stability: 10 ml of the ultra-high molecular weight silicone-modified acrylate emulsion of each embodiment and comparative example was respectively measured and filtered and placed in a centrifuge tube, centrifuged at 3000 r / min for 15 min, the centrifuge tube was taken out, filtered again, and whether there was any residue left on the filter screen.

[0100] Electrolyte stability: Take 16 conical flasks, add 0.5g of calcium chloride to 100g of distilled water to prepare a solution, then add 25g of the ultra-high molecular weight silicone-modified acrylate emulsion of each embodiment and comparative example, stir evenly and let stand at the same room temperature for 24h to observe whether there is demulsification. If there is no demulsification, it proves that the electrolyte stability of the emulsion has passed.

[0101] Particle distribution: 1 ml of ultra-high molecular weight silicone modified acrylate emulsion of each embodiment and comparative example was placed in a laser dynamic light scattering instrument (MS800), and the same emulsion was measured three times continuously, and the experimental data were recorded and analyzed. During the continuous test, an increase in light intensity means that the emulsion particles are aggregated, a decrease in light intensity means that the emulsion particles are dissolved, and irregular changes in light intensity mean that the emulsion particles are unstable. The measurement error of light intensity is within 10%.

[0102] The experimental results are shown in Table 3.

[0103] Table 3 Emulsion performance test results

[0104]

[0105] The experimental results show that the core-shell structured ultra-high molecular weight silicone modified acrylate emulsion prepared by using an emulsifier prepared by mixing alkyl polyoxyethylene ether ammonium sulfate, fatty alcohol polyoxyethylene ether sodium sulfosuccinate and nonylphenol polyoxyethylene ether in a mass ratio of 5:(1-3):(2-5) has a better emulsifying effect, and the prepared ultra-high molecular weight silicone modified acrylate emulsion has better emulsification effect.

[0106] The ultra-high molecular weight silicone-modified acrylate emulsion prepared by using an initiator compounded with ammonium persulfate, potassium persulfate and sodium persulfate in a mass ratio of 7:(2-3):(2-5) has a better core-shell encapsulation effect and can further disperse the emulsion particles in the emulsion.

[0107] The ultra-high molecular weight silicone-modified acrylate emulsion prepared by compounding acidic monomers of maleic acid, cinnamic acid, citric acid and maleic anhydride in a mass ratio of 3:(1-2):(0.5-1):(3-5) can inhibit the mutual reaction of silane molecules on the silane coupling agent, thereby reducing the mutual reaction of the hydrolyzable groups contained in the silane coupling agent after hydrolysis, reducing the aggregation phenomenon between emulsion particles, and further improving the stability of the ultra-high molecular weight silicone-modified acrylate emulsion.

[0108] In the preparation process of ultra-high molecular weight silicone modified acrylate emulsion, the emulsion prepared by the reaction at a water bath temperature of 80°C has better effect, good dispersion of emulsion particles, and no aggregation between emulsion particles.

[0109] The technical solution of adding a silane coupling agent into the core layer emulsion and adding a silicone polymer into the shell layer can further reduce the aggregation phenomenon between the emulsion particles, further improve the stability of the ultra-high molecular weight silicone-modified acrylate emulsion, and further improve the adhesion between the ultra-high molecular weight silicone-modified acrylate emulsion and the silicon-based negative electrode.

[0110] Experiment 2

[0111] The rotational viscometer tests the viscosity of ultra-high molecular weight silicone-modified acrylate emulsions. By testing the viscosity of ultra-high molecular weight silicone-modified acrylate emulsions, it is possible to further infer whether it has excellent dispersion effects on active substances and conductive agent particles when used as a binder.

[0112] Experimental method: The viscosity was measured using a NDJ-9S viscometer (Shanghai Fangrui Instrument Co., Ltd.). The ultra-high molecular weight silicone modified acrylate emulsions of each experimental example and comparative example were poured into beakers, and the No. 1 rotor of the NDJ-9S viscometer was used to measure the viscosity. During the measurement, the liquid level of the ultra-high molecular weight silicone modified acrylate emulsion was ensured to be aligned with the scale of the rotor. After the ultra-high molecular weight silicone modified acrylate emulsion was stable, the viscosity value was read. The experimental results are shown in Table 4.

[0113] Table 4 Viscosity of ultra-high molecular weight silicone-modified acrylic emulsion

[0114]

[0115]

[0116] The experimental results show that the ultra-high molecular weight silicone-modified acrylic emulsion prepared by the preparation method of Examples 1-11 has better viscosity, a larger molecular weight, and an excellent effect of dispersing active substances and conductive agent particles.

[0117] In Comparative Example 3, the technical solution of adding a silane coupling agent to the shell layer emulsion and adding an organosilicon polymer to the core layer is adopted, which will inhibit the penetration of the shell layer emulsion into the core layer emulsion, reduce the reaction rate between the organic functional groups in the silane coupling agent and the organosilicon polymer, reduce the mechanical stability of the core-shell structure, and reduce the molecular weight of the ultra-high molecular weight organosilicon-modified acrylate emulsion compared with the embodiment. The adhesion between the ultra-high molecular weight organosilicon-modified acrylate emulsion and the silicon-based negative electrode is lower than that of the embodiment.

[0118] Experiment 3

[0119] The HY-0350 lithium battery peeling tester is used to test the strength of the bonding force of the binder to the negative electrode.

[0120] Experimental methods:

[0121] Preparation of negative electrode sheets: Mix nano Si powder, conductive agent and the ultra-high molecular weight silicone modified acrylate emulsion of the above-mentioned experimental examples and comparative examples into a uniform negative electrode slurry, and the mixing mass ratio is: nano Si powder: conductive agent: ultra-high molecular weight silicone modified acrylate emulsion is 6:2:2. Use a medical scraper to coat it on a single-sided smooth copper foil, place the coated copper foil in a vacuum drying oven at 80°C and dry it for 12 hours. After drying, use a manual slicer to cut the dried electrode sheet into 19mm*70mm negative electrode sheet strips.

[0122] Assembly of lithium battery: A lithium battery is assembled by assembling the negative electrode sheet and the positive electrode (lithium sheet), a separator, a shell, and an electrolyte. The assembly and preparation methods are well known in the art and will not be described in detail here.

[0123] Use pressure-sensitive 3M-VHB double-sided tape to fix the negative electrode strips on the stainless steel plate. Fix the stainless steel plate on the two fixtures of the lithium battery peeling tester, and then perform a 180° peeling test at a speed of 50mm / min and a load of 50N. The force detected when the copper foil is completely peeled off is the peeling force. During the test, the negative electrode strips before use and the negative electrode strips after 100 cycles are tested respectively. The test results are based on the average peeling force in the length direction, and the unit is N. Peel strength change rate (%) = [(average peeling force before test - average peeling force after 100 cycles) / average peeling force before test] * 100%, the test results are shown in Table 5.

[0124] Table 5 Mechanical peeling force test results

[0125]

[0126]

[0127] The experimental results show that when the ultra-high molecular weight silicone-modified acrylate emulsion prepared by the preparation method of Examples 1-11 is used as a binder, it has excellent negative electrode adhesion and excellent effect in inhibiting silicon expansion, can effectively enhance the mechanical strength of the negative electrode, buffer the mechanical stress during the silicon volume expansion process, and improve the service life of the lithium battery.

[0128] Experiment 4

[0129] The lithium battery assembled in Experiment 3 was used as the experimental sample for charge and discharge tests.

[0130] Experimental method: Constant current charge / discharge range: 0.01~1.0V, test the first discharge capacity, first coulomb efficiency, discharge capacity and discharge capacity retention rate of the lithium battery after 100 cycles, and the test results are shown in Table 6 below.

[0131] Table 6 Lithium battery charge and discharge test results

[0132]

[0133] The experimental results show that when the ultra-high molecular weight silicone-modified acrylate emulsion prepared by the preparation method of Examples 1-11 is used as a binder, the binding force between the silicon atoms contained therein and the silicon-based negative electrode can be significantly enhanced, and the mechanical strength of the negative electrode is enhanced by increasing the amount of chemical crosslinking between the alkoxy structure contained therein and the negative electrode substrate. The volume expansion of silicon can be effectively inhibited, the mechanical stress during the volume expansion of silicon can be buffered, and the solid electrolyte intermediate phase produced by the contact reaction of silicon with the electrolyte during the continuous expansion process is reduced, and the side reactions caused by the unstable solid electrolyte intermediate phase are effectively eliminated, which significantly improves the initial coulomb efficiency and cycle performance of the lithium battery, effectively prolongs the service life of the lithium battery, and improves the safety performance of the lithium battery.

[0134] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. An ultra-high molecular weight silicone-modified acrylic emulsion, characterized in that: The ultra-high molecular weight silicone modified acrylate emulsion is polymerized by core-shell emulsion polymerization technology. The ultra-high molecular weight silicone modified acrylate emulsion includes a core layer emulsion and a shell layer emulsion, wherein the core layer emulsion includes the following raw materials in parts by weight: Structural monomer: 30~50 parts; Acidic monomer: 1~5 parts; Deionized water: 60~80 parts; Initiator: 0.1~1.2 parts; Emulsifier: 0.4~1.8 parts; Silane coupling agent: 0.1~5 parts; The shell emulsion comprises the following raw materials in parts by weight: Structural monomer: 30~50 parts; Acidic monomer: 1~5 parts; Deionized water: 10~20 parts; Initiator: 0.5~1.2 parts; Emulsifier: 0.4~1.8 parts; Silicone polymer: 0.1~5 parts; The structural monomers in the core layer emulsion and the shell layer emulsion are a combination of one or more of methyl acrylate, ethyl acrylate, isobutyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, isobornyl acrylate, methyl methacrylate, butyl methacrylate, acrylonitrile, acrylamide, styrene, vinyl acetate, and isobornyl methacrylate; The acidic monomers in the core layer emulsion and the shell layer emulsion are maleic acid, cinnamic acid, citric acid, and maleic anhydride in a mass ratio of 3: (1-2): (0.5-1): (3-5); Wherein, the silane coupling agent is a compound of one or more of methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, methylallyltrimethoxysilane and vinyltriacetoxysilane; The organosilicon polymer is a compound of one or more of vinyl silane oligomer, vinyl MQ organosilicon resin, vinyl silicone rubber, vinyl silicone oil, methacryloxy silane oligomer, and acryloxy MQ silicone resin.

2. The ultra-high molecular weight silicone-modified acrylate emulsion according to claim 1, characterized in that: The core layer emulsion comprises the following raw materials in parts by weight: Structural monomer: 32~43 parts; Acidic monomer: 2~3 parts; Deionized water: 60~70 parts; Initiator: 0.2~0.5 parts; Emulsifier: 0.5~1 part; Silane coupling agent: 0.5~3 parts; The shell emulsion comprises the following raw materials in parts by weight: Structural monomer: 32~43 parts; Acidic monomer: 2~3 parts; Deionized water: 10~15 parts; Initiator: 0.8~1 part; Emulsifier: 0.5~0.8 parts; Silicone polymer: 0.5~3 parts; The structural monomers in the core layer emulsion and the shell layer emulsion are a combination of one or more of ethyl acrylate, butyl acrylate, 2-isooctyl acrylate, isobornyl acrylate, methyl methacrylate, butyl methacrylate and acrylonitrile.

3. The ultra-high molecular weight silicone-modified acrylate emulsion according to claim 1, characterized in that: The initiator is a combination of one or more of ammonium persulfate, potassium persulfate, sodium persulfate, and 2,2'-azobisisobutylamidine dihydrochloride.

4. The ultra-high molecular weight silicone-modified acrylate emulsion according to claim 3, characterized in that: The initiator is ammonium persulfate, potassium persulfate and sodium persulfate mixed in a mass ratio of 7:(2-3):(2-5).

5. The ultra-high molecular weight silicone-modified acrylate emulsion according to claim 1, characterized in that: The emulsifier is prepared by mixing alkyl polyoxyethylene ether ammonium sulfate, fatty alcohol polyoxyethylene ether sodium sulfosuccinate and nonylphenol polyoxyethylene ether in a mass ratio of 5: (1-3): (2-5).

6. An ultra-high molecular weight silicone-modified acrylate emulsion according to any one of claims 1 to 5, characterized in that: The solid content of the ultra-high molecular weight silicone-modified acrylic emulsion is 38% to 65%.

7. A method for preparing an ultra-high molecular weight silicone-modified acrylate emulsion as claimed in any one of claims 1 to 6, comprising the following steps: (1) Mix 30% to 50% of the emulsifier, 30% to 50% of deionized water, structural monomers, silane coupling agents, and acidic monomers in the core layer emulsion formula and mechanically stir until milky white to obtain a core layer pre-emulsion; (2) Under nitrogen atmosphere, the remaining deionized water, initiator, and remaining emulsifier in the core layer emulsion formula are mixed and mechanically stirred and placed in a water bath, and then the core layer pre-emulsion is added dropwise thereto, the dropping time is controlled at 2h~4h, and the reaction temperature is 70~80°C to obtain a core layer emulsion; (3) mixing the emulsifier, deionized water, structural monomer, organosilicon polymer, and acidic monomer in the shell emulsion formula and mechanically stirring until the mixture turns milky white to obtain a shell pre-emulsion; (4) Add the initiator in the shell layer emulsion formula to the core layer emulsion, and then slowly add the shell layer pre-emulsion to the core layer emulsion. The dropping time is controlled at 2h~4h, the reaction temperature is 70~80℃, and it is kept at 83~87℃ for 1h, then cooled to room temperature, filtered and discharged to obtain an ultra-high molecular weight silicone modified acrylate emulsion.

8. The method for preparing an ultra-high molecular weight silicone-modified acrylate emulsion according to claim 7, characterized in that: The reaction temperature in step (2) is controlled at 80°C; The reaction temperature in step (4) is controlled at 80°C.

Citation Information

Patent Citations

  • Preparation method of nuclear shell structure high-silicon silicone acrylic emulsion used for building exterior wall

    CN101781390A

  • Oil-in-water emulsion cosmetic composition

    CN112689500A